CURRENT CYSTIC DUCT CLOSURE METHODS AND THEIR IMPACT ON COMPLICATIONS LAPAROSCOPIC CHOLECYSTECTOMY (Ustozlar uchun, 2026)
For the surgical treatment of gallbladder disorders, laparoscopic cholecystectomy (LC) has emerged as the gold standard in recent years. However, a review of the literature shows that there is still a considerable risk of problems, especially bile leakage.Materials and Methods: With a focus on cystic duct management strategies during LC, this research examined scholarly literature, including original papers, systematic reviews, and meta-analyses. Comparing contemporary approaches, including vessel-sealing devices, with conventional ligation and clipping procedures received special attention.